2009
DOI: 10.1111/j.1365-2125.2009.03516.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymorphism in ABCB1 gene, CYP2B6*6 and sex predict single‐dose efavirenz population pharmacokinetics in Ugandans

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Efavirenz is metabolized by highly polymorphic enzymes, CYP2B6 and CYP3A. The effect of the different variant alleles on efavirenz population pharmacokinetics has not yet been fully explored.• CYP2B6*6 influences efavirenz steady-state pharmacokinetics. Together with sex it explains 11% of the between-subject variability in apparent oral clearance, but predictions could potentially be improved if additional alleles causing reduced drug metabolism were identified.• ABCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
135
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 32 publications
14
135
6
Order By: Relevance
“…In another Ugandan population, the 516G4T and 785A4G SNPs were found in 35.6 and 36.4% of the population, respectively (Mukonzo et al, 2009). Ngaimisi et al (2013) found the frequency of the 516G4T SNP to be significantly higher in Tanzanians (41.8%) than Ethiopians (31.4%), with 18.6% compared to only 8.7% homozygous individuals in the Tanzanian and Ethiopian populations, respectively.…”
Section: Cyp2b6*6 (516g4t and 785a4g)mentioning
confidence: 99%
See 2 more Smart Citations
“…In another Ugandan population, the 516G4T and 785A4G SNPs were found in 35.6 and 36.4% of the population, respectively (Mukonzo et al, 2009). Ngaimisi et al (2013) found the frequency of the 516G4T SNP to be significantly higher in Tanzanians (41.8%) than Ethiopians (31.4%), with 18.6% compared to only 8.7% homozygous individuals in the Tanzanian and Ethiopian populations, respectively.…”
Section: Cyp2b6*6 (516g4t and 785a4g)mentioning
confidence: 99%
“…An increase in efavirenz concentration is associated with an increase in the number of loss of function alleles, namely, CYP2B6 *6, *18, *20 and *27, in both Zimbabwean and Ugandan populations, with the number of either the 516G4T or 983T4C alleles having the greatest impact on increasing efavirenz concentrations (Jamshidi et al, 2010). Mukonzo et al (2009) reported a 21% lower oral clearance of efavirenz in another Ugandan population for individuals homozygous for the *6 allele. In a Bantu-speaking South African HIV-positive population, 35% had plasma efavirenz levels above the therapeutic range of 4 mg/ml, which is likely to be associated with toxicity (Swart et al, 2013).…”
Section: Cyp2b6*6 (516g4t and 785a4g)mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, studies have also been done in African populations to evaluate the clinical implications of the CYP2B6*6 allele in the use of efavirenz [15][16][17][18], and nevirapine [19][20][21]. CYP2B6*6 has been associated with higher efavirenz plasma concentrations due to lower clearance rates, which may lead to CNS side effects [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Halflives were highly variable (21,22), and as expected, they were shorter than the half-life reported after administration of a single dose (6), as a consequence of the autoinduction property of efavirenz. A genetic polymorphism of CYP2B6 G516T (4,6,10,14,16,17,20,23) leads to prolonged efavirenz half-lives and has been recognized as a factor that may explain the variability of efavirenz pharmacokinetics (5,21). Unfortunately, at the time the study was designed, blood samples were not collected for pharmacogenetics, and the ethnicity of patients was not recorded.…”
mentioning
confidence: 99%